(untitled) (International Journal of Food and Nutritional Sciences, 2023)
The “Geo Spatial big data” has a collective term. It is very difficult, complicated and complex to analyze the Diverse, enormous, invariable semi-structured or unstructured digital material by using typical DBMS tools and methodology. This data is also known as semi-structured data. Using “Geo Spatial big data techniques” the main goals are: providing best decision making, by increasing efficiency to reduce cost, the presence of real time assistance and spatial link analyses. The research methodology depends upon the reviewed research. If we talk about the trends of Geo Spatial big data analytics application- First is conceptual method and in this method we will see about data processing, overlay analysis, the prediction of changes in land use, land analysis on Global Scale. In the field of Data Mining, the second focus pertains to the study of human mobility and disaster management. The third area of interest involves knowledge representation, including problem-solving, Geo-Spatial knowledge representation, and the exploration of big data.